2017
DOI: 10.1186/s13075-017-1485-8
|View full text |Cite
|
Sign up to set email alerts
|

Progranulin derivative Atsttrin protects against early osteoarthritis in mouse and rat models

Abstract: BackgroundAtsttrin, an engineered protein composed of three tumor necrosis factor receptor (TNFR)-binding fragments of progranulin (PGRN), shows therapeutic effect in multiple murine models of inflammatory arthritis . Additionally, intra-articular delivery of PGRN protects against osteoarthritis (OA) progression. The purpose of this study is to determine whether Atsttrin also has therapeutic effects in OA and the molecular mechanisms involved.MethodsSurgically induced and noninvasive rupture OA models were est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
51
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(53 citation statements)
references
References 58 publications
(86 reference statements)
2
51
0
Order By: Relevance
“…Additionally, in control with absence of PGRN, grafts were at high risk of being damaged. As a result, PGRN is considered to be a promising prophylactic and therapeutic target for various arthritis associated diseases . Based on these studies, we hypothesize that PGRN may play a role in the pathogenesis and development of articular changes in patients suffering from haemophilia.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Additionally, in control with absence of PGRN, grafts were at high risk of being damaged. As a result, PGRN is considered to be a promising prophylactic and therapeutic target for various arthritis associated diseases . Based on these studies, we hypothesize that PGRN may play a role in the pathogenesis and development of articular changes in patients suffering from haemophilia.…”
Section: Introductionmentioning
confidence: 95%
“…Furthermore, a PGRN‐deficient (PGRN −/− ) mouse model led to the spontaneous development of OA‐like pathological changes, which were mitigated after introduction of recombinant PGRN (rPGRN) . Wei et al demonstrated therapeutic effect of Atsttrin (protein composed of three tumour necrosis factor receptor (TNFR)‐binding fragments of progranulin) in inflammatory arthritis on murine models. Lau et al performed a study with transgenic living hyaline cartilage graft releasing progranulin.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, PGRN functions as a physiological antagonist of TNFR1 and a potent agonist of TNFR2 (with approximately 600‐fold higher binding affinity to TNFR2 than TNF). PGRN and Atsttrin, an engineered peptide consisting of the domains and adjacent linker regions of PGRN responsible for interacting with TNFRs, appear to have strong anti‐inflammatory properties and were shown to mediate protective and anabolic effects in mouse models of osteoarthritis and inflammatory arthritis . Moreover, PGRN was shown to have protective and therapeutic effects in additional inflammatory disease models, including IBD, psoriasis, diabetes mellitus, systemic lupus erythematosus, and others .…”
Section: Selective Tnf Blockadementioning
confidence: 99%
“…PGRN and Atsttrin, an engineered peptide consisting of the domains and adjacent linker regions of PGRN responsible for interacting with TNFRs, appear to have strong anti-inflammatory properties and were shown to mediate protective and anabolic effects in mouse models of osteoarthritis and inflammatory arthritis. 36,91 Moreover, PGRN was shown to have protective and therapeutic effects in additional inflammatory disease models, including IBD, psoriasis, diabetes mellitus, systemic lupus erythematosus, and others. 92 A very recent publication has also demonstrated the ability of Atsttrin to inhibit TNF-mediated catabolism in a murine ex vivo model of intervertebral disk degeneration, supporting the protective effect of Atsttrin in TNF-driven inflammatory conditions impacting the axial skeleton.…”
Section: Selective Tnf Blockadementioning
confidence: 99%
“…15 In preliminary studies, Atsttrin proofed to have therapeutic effect in models of inflammatory arthritis, 14,15 inflammatory bowel disease, 16 and showed protective effects in bone healing and osteoarthritis. 17 In consideration of this possible proinflammatory role of PGRN-Abs and given the frequent occurrence of PGRN-Abs in the course of SLE, the present study was aimed to examine PGRN-Abs in serum of patients with systemic sclerosis and other autoimmune connective tissue disorders.…”
Section: Introductionmentioning
confidence: 99%